Republic of Kazakhstan : 2007 Article IV Consultation-Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
The 2007 Article IV Consultation on the Republic of Kazakhstan focuses on the appropriate policy response to mounting banking sector risks and continuing inflation pressures. Banking sector risks are mounting and inflation remains relatively high. The authorities intend to continue raising policy interest rates gradually. The Financial Supervision Agency's (FSA) powers have been enhanced and a sizable increase in its resources is expected shortly. Monetary tightening and exchange rate appreciation are needed to contain risks and dampen inflation.